How does imported pork regulate the supply and demand of China's pig market during the epidemic?—based on the analysis of African swine fever and COVID-19 - Wang, Jingjing; Wang, Gangyi; Cui, Yiniu; Zhang, Jie (Frontiers in Veterinary Science, 2022)
China's hog industry is a domestic demand-led economy, and ensuring domestic pork supply is the primary goal of the development of the pig industry .Taking the pork imports of China as the research object, this paper analyzed the changes in Chinese pork imports and its dynamic process under the outbreak of African Swine Fever (ASF) and COVID-19 from January 2017 to November 2020, evaluated the impact of imported pork on the development of the hog industry in China. The results show that: The shortage of domestic pork supply changes the import volume. ASF makes imported pork transform from a complementary product to meet the diversified needs of domestic consumers into a substitute to fill the supply gap. After the outbreak of COVID-19, the substitution effect of imported pork decreases. Under the ASF, the supply capacity of pork in China decreased, the price increased, and the change in the mode of pig transportation pushed the import of pork up in January 2019. At the end of 2019, pig slaughter was lower, while China cut tariffs on imported pork. The COVID-19 outbreak did not reduce China's pork imports, which declined after the global COVID-19 outbreak. Imported pork has made up for the supply gap during COVID-19, leaving no impact on the hog industry in China.